ДІАГНОСТИКА СИСТЕМИ УПРАВЛІННЯ РИНКОМ ПРАЦІ В СУЧАСНИХ УМОВАХ - Vuychenko, Maryna (Zhytomyr Ivan Franko State University, 2022)
The article states that under the objective conditions of economic development, expansion of types of individual labor activity, changes in organizational management structures, reduction and modernization of methods and methods of state intervention in economic activity, measures to ensure social guarantees to the population are necessary not only by the state, but also by bodies Local Government. These measures should represent guarantees to each representative of the territorial community for a certain level of benefits and services at the expense of both their own contributions and the redistribution of resources among the population for the purpose of its material support. Attention is drawn to the fact that the current legislation, in its majority, focuses exclusively on the public needs of the state, which is manifested in the dominance of measures that are related to the adoption of decisions that are populist in nature and do not solve the existing problems of the population. It is emphasized that the development and introduction of new forms and types of social protection are not always able to positively influence the achievement of real results. This is due to the low efficiency of the current legislation in the direction of social security of the population, as well as the high level of violation of the rights of the specified category of society, in particular, by the state itself and its authorized bodies. This is precisely why the issue of managing the social protection of the population is highly relevant. The article determines that the decisive role in the management of social and labor relations certainly belongs to the state.It is the state that guarantees able-bodied citizens permanently residing in Ukraine a free choice of types of work, free assistance by state employment services in the employment of workers in accordance with their education and qualifications, abilities and vocations, as well as the real needs and requirements of employers for the quality of workers and the state of the labor market .